2009
DOI: 10.1179/174313209x395463
|View full text |Cite
|
Sign up to set email alerts
|

Variations in the effects on synthesis of amyloidβprotein in modulated autophagic conditions

Abstract: The biochemical pathways leading to autophagy and the generation of AVs appear to be different in cells treated by the three methods. These differences may explain why the similar autophagic status determined by LC3 immunoreactivities does not correlate with Abeta generation and secretion.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
4
0

Year Published

2010
2010
2018
2018

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 40 publications
2
4
0
Order By: Relevance
“…Our study further reveals that in a manner similar to treatment with U18666A, cholesterol supplementation of the culture medium, as shown in a recent study (66), increases the intracellular levels of APP, APP CTFs, and A␤ in APPsw cells, possibly by enhancing cellular accumulation of cholesterol. We also showed that U18666A treatment, as reported earlier (31,72,73,75), can enhance the levels of LC3-II, suggesting an impaired autophagic pathway following EL cholesterol sequestration. Interestingly, the levels of APP and its metabolites are not found to be altered when cells are cotreated with U18666A and 3-MA compared with those treated with U18666A alone.…”
Section: Discussionsupporting
confidence: 85%
See 2 more Smart Citations
“…Our study further reveals that in a manner similar to treatment with U18666A, cholesterol supplementation of the culture medium, as shown in a recent study (66), increases the intracellular levels of APP, APP CTFs, and A␤ in APPsw cells, possibly by enhancing cellular accumulation of cholesterol. We also showed that U18666A treatment, as reported earlier (31,72,73,75), can enhance the levels of LC3-II, suggesting an impaired autophagic pathway following EL cholesterol sequestration. Interestingly, the levels of APP and its metabolites are not found to be altered when cells are cotreated with U18666A and 3-MA compared with those treated with U18666A alone.…”
Section: Discussionsupporting
confidence: 85%
“…Thus, to determine whether APP metabolism regulated by U18666A treatment is partly mediated by the autophagic pathway, we treated APPsw cells with U18666A in the presence or absence of the autophagy inhibitor 3-MA. Consistent with earlier data (31,(72)(73)(74)(75), the treatment with U18666A increased the levels of the autophagy marker LC3-II, which was accompanied by enhanced levels of APP, APP CTFs, and A␤ 1-40 ( Fig. 15A to H).…”
Section: Fig 12supporting
confidence: 91%
See 1 more Smart Citation
“…Failure to clear of Aβ, generated from AVs, leads to Aβ accumulation in AD (Yu et al, 2004; Nixon, 2007). AVs are colocalized within Aβ deposits (Pajak et al, 2009), and AVs may be sites of Aβ generation (Mizushima, 2005; Makioka et al, 2009). The immature autophagolysosomes and the arrest of their retrograde transport contribute to a massive accumulation of AVs within Aβ degenerating neuritis (Nixon, 2007).…”
Section: Autophagy and Aβmentioning
confidence: 99%
“…In pathology, a decreased mTOR signaling pathway contributes to the formation of autophagosomes, accumulated in AD, accompanied by reduced Aβ levels (Yoon et al, 2008). Increasing Aβ can trigger the mTOR signaling via a PRAS40‐mediated mechanism (Caccamo et al, 2011) and then lower the autophagic activity (Makioka et al, 2009; Shen et al, 2011). Inhibition of mTOR by rapamycin retards cognitive deficits and reduces Aβ pathology by increasing autophagy in AD models (Caccamo et al, 2010; Spilman et al, 2010; Table I).…”
Section: Mtor: a Valid Therapeutic Target Through The Autophagy Pathwmentioning
confidence: 99%